Diagnosis Recording Accuracy and Coding Accuracy in Hospitalization: Ketepatan Pencatatan Diagnosis dan Ketepatan Kode Diagnosis dalam Rawat Inap - Utami, Yeni Tri; Maryati, Warsi; Astikasari, Salsa (Procedia of Engineering and Life Science, 2025)
The accuracy of diagnosis recording can affect the accuracy of coding. If the diagnosis written by the doctor is unclear, the coder will have difficulty in determining the diagnosis code. Based on the results of an initial survey at PKU Muhammadiyah Wonogiri Hospital, the accuracy of diagnosis recording was 50% and the accuracy of diagnosis coding was 50%. This study aims to determine the relationship between the accuracy of diagnosis recording on the medical resume sheet and the accuracy of inpatient case coding. This type of research is analytical with a cross-sectional approach design. The population was 1,036 DRM and a sample of 92 DRM with a simple random sampling technique. Data analysis was univariate and bivariate analysis using the chi-square statistical test. The results showed that the accuracy of diagnosis recording on the medical resume sheet was 54% greater than the inaccuracy of 46%, while the accuracy of inpatient coding was greater at 71% compared to the inaccuracy of 29%. The results of the chi-square test using the SPSS 23 application showed a p-value of 0.032 < 0.05, which means there is a relationship between the accuracy of recording diagnoses on the medical resume sheet and the accuracy of coding inpatients at PKU Muhammadiyah Wonogiri Hospital. It is recommended that coders be more careful in reading diagnoses and reviewing the results of supporting examinations to avoid coding errors and update the list of disease abbreviations more comprehensively to standardize doctors in recording diagnoses.